HLA‐DR⁺ Tumor Cells Show an Association with a Distinct Immune Microenvironment and CD8⁺ T‐Cell Exhaustion in HBV‐Associated Hepatocellular Carcinoma - Jun‐Qing Chang; Yan Guo; Wen‐Jing Yuan; Yu‐Man Chen; Bo‐Wei Liu; Wen‐Tao Li; Xiang‐Ming Ding; Xu‐Dong Fu; Yu‐Han Lou; Zhuo‐Ran Chen; Xiao‐Ying Luo; Song‐Ze Ding; et al. (Advanced Science)
Abstract Hepatocellular carcinoma (HCC) is a leading cause of cancer‐related deaths worldwide, with hepatitis B virus (HBV) as a major driver. Despite the pivotal role of viral infections in shaping the tumor microenvironment (TME), the mechanistic differences among HBV‐, hepatitis C virus (HCV)‐, and non‐B non‐C (NBNC)‐associated HCC remain poorly understood. By integrating the largest publicly available single‐cell RNA sequencing (scRNA‐seq) dataset of HCC (160 samples from 124 patients) with multi‐scale protein‐level validation using multiplex immunofluorescence and tissue microarrays (198 HCC specimens), HLA‐DR⁺ tumor cells are identified as a distinctive feature of HBV+HCC. These tumor cells uniquely express MHC class II molecules, typically restricted to antigen‐presenting cells, and correlate with immune checkpoint activation and PD‐L1 expression, potentially contributing to an immunosuppressive microenvironment specific to HBV+HCC. Trajectory analysis revealed distinct CD8⁺ T‐cell differentiation pathways in HBV+HCC, characterized by enhanced exhaustion and stem‐like phenotypes. HLA‐DR⁺ tumor cells are associated with increased recruitment of CD8⁺ T cells and correlated with T‐cell exhaustion, potentially contributing to a suppressive TME. Clinically, high proportions of HLA‐DR⁺ tumor cells are linked to poor survival outcomes, especially when accompanied by elevated PD‐L1 expression, suggesting that HLA‐DR⁺ tumor cells may serve as a potential predictive biomarker for immunotherapy efficacy in HCC. Collectively, the findings highlight HLA‐DR⁺ tumor cells as a distinctive feature of HBV‐associated HCC (HBV+HCC), providing novel insights into possible immunosuppressive mechanisms and therapeutic targets for immunotherapy in this disease context.